Reduced-Size Series-Fed Two-Dipole Endfire Antenna - Wang, Heesu; Park, Yong Bae; Park, Ikmo (Journal of Electromagnetic Engineering and Science, 2022)
The conventional series-fed endfire dipole antenna has a wide impedance bandwidth and is inexpensive to manufacture. However, it has a disadvantage: its size is large because of the large inter-dipole spacing, which is required to satisfy the endfire condition for good antenna radiation characteristics. Here, we propose a two-dipole endfire antenna with a reduced size. The miniaturized endfire antenna was designed using a meander line to reduce the interdipole spacing while ensuring that the endfire condition was satisfied. Furthermore, the overall width of the antenna was reduced using a bent dipole and a corrugated ground plane. The electrical size of the proposed antenna was only 0.33λ0 x 0.33λ0 x 0.014λ0 at a center frequency of 5 GHz, its –10 dB impedance bandwidth was 4.47–5.72 GHz (24.5%), and the gain at the center frequency was 5.9 dBi.
Keywords: C-band antenna; Dipole antenna; Endfire antenna; Miniaturized antenna; Printed dipole antenna